Immune cell-mediated features of atherosclerosis - Liu, Tingting; Chen, Yanjun; Hou, Lianjie; Yu, Yulu; Ma, Dan; Jiang, Ting; Zhao, Guojun (Frontiers in Cardiovascular Medicine, 2024)
Atherosclerosis is a chronic inflammatory disease characterized by innate and adaptive immune responses, which seriously threatens human life and health. It is a primary cause of coronary heart disease, myocardial infarction, and peripheral vascular disease. Research has demonstrated that immune cells are fundamental to the development of atherosclerosis and chronic inflammation. Therefore, it is anticipated that immunotherapy targeting immune cells will be a novel technique in the management of atherosclerosis. This article reviews the growth of research on the regulatory role of immune cells in atherosclerosis and targeted therapy approaches. The purpose is to offer new therapeutic approaches for the control and treatment of cardiovascular illnesses caused by atherosclerosis.